Persepsi Remaja Tentang Tayangan Program HSS (Holywings Sport Show ) di NET TV - Miranti Eltari; Yenrizal Yenrizal; Sepriadi Saputra (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Holywing Sport Show Is a sports show that was established in an attractive Entertainment package that can be a different kind of interesting entertainment for viewers and of course encourage the positive growth of martial arts in Indonesia and can encourage the potential of boxing in Indonesia, which had suspended animation in this match. Many teenagers in Kelurahan 15 Ulu like this show as entertainment for them. This research method uses a quantitative approach with frequency distribution analysis. Quantitative approach is a research in which the results will be presented in the form of a description and by using numbers. After doing the research According to the Used and Gratification Theory with the theoretical assumption that Supervision is the satisfaction that comes from the use of media in the form of gathering the required information. The results of this study can be concluded that teenagers in the 15 Ulu sub-district like the match between Paris Fernandes and Jakson Karmela. Aimed at